Die "hyggeligen" Dänen und die arroganten Deutschen - kommunikative Unterschiede als Konsequenz nationaler Stereotype? - Hulgaard, Anne Marie (HERMES - Journal of Language and Communication in Business, 2022)
The “hyggelige” Danes and the arrogant Germans – Communicative Differences as a Consequence of National Stereotypes? The aim of this article is to discuss why German students code switch between German and Danish in a more appropriate way than their Danish fellow students do. The data consist of approximately 230 emails written by 40 German and Danish students enrolled in the Cross-Border Study Programme at the University of Southern Denmark and Europa-Universität Flensburg. A reason for this difference in ability to switch code can be explained by the students’ stereotypes about their own group as auto stereotypes and about the others as hetero stereotypes. In general, Danish auto stereotypes are very positive contrary to the negative hetero stereotypes of the Germans. Because of this, the Danish students seem to think that it is acceptable to use Danish communication structures even though they know that the chosen formulation will not be seen as appropriate German by their German professors.